Pengaruh Kepuasan Kerja dan Motivasi terhadap Kinerja Karyawan Perusahaan Daerah Air Minum (PDAM) Muara Teweh Kabupaten Barito Utara - Sundusiah Sundusiah; Hairudinor Hairudinor; M. Nur Iman Ridwan (Universitas Lambung Mangkurat, 2019)
This study aimed to examine the effect of job satisfaction (X1) and Motivation (X2) of the Employee Performance (Y) on the Perusahaan Daerah Air Minum (PDAM) Muara Teweh Kabupaten Barito Utara. Samples taken as many as 54 employees were selected with saturated sampling technique. Collecting data using questionnaires, while data analysis using SPSS. The test results prove job satisfaction significantly influence employee performance with large partially apengaruhnya 37.2% and Motivation significant effect on employee performance partially to great effect 57.3%, while simultaneously Job Satisfaction and Motivation significant effect on employee performance with great the effect of 26.7% while the remaining 73.3% is influenced by other variables. Keywords: Job Satisfaction, Motivation, Employee Performance